2016
DOI: 10.1186/s12967-016-0930-9
|View full text |Cite
|
Sign up to set email alerts
|

New perspective in diagnostics of mitochondrial disorders: two years’ experience with whole-exome sequencing at a national paediatric centre

Abstract: BackgroundWhole-exome sequencing (WES) has led to an exponential increase in identification of causative variants in mitochondrial disorders (MD).MethodsWe performed WES in 113 MD suspected patients from Polish paediatric reference centre, in whom routine testing failed to identify a molecular defect. WES was performed using TruSeqExome enrichment, followed by variant prioritization, validation by Sanger sequencing, and segregation with the disease phenotype in the family.ResultsLikely causative mutations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
184
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(202 citation statements)
references
References 68 publications
17
184
1
Order By: Relevance
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 62%
“…Although liver respiratory chain activity was normal, there was evident liver dysfunction. Liver involvement was also described in six additional EARS2 patients, which included one or more of neonatal transient icterus, hepatomegaly, fatty liver and steatosis (Steenweg et al 2012;Talim et al 2013;Taylor et al 2014;Pronicka et al 2016). Post-mortem examination of the liver from the patient reported by Talim et al (2013) also found COXdeficiency.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, whole exome sequencing has revealed homozygous SLC19A3 c.74dupT (p.Ser26Leufs*19) mutation. Molecular analysis performed in his family confirmed parental inheritance of the identified variant [13].…”
Section: Case Reportsmentioning
confidence: 63%
“…Two Polish patients with the SLC19A3 mutations identified out of 113 mitochondrial patients studied in The Children's Memorial Health Institute (CMHI) in the period of 1995-2016 [13] were included.…”
Section: Methodsmentioning
confidence: 99%